First Report of a Mesonivirus and Its Derived Small RNAs in an Aphid Species Aphis citricidus (Hemiptera: Aphididae), Implying Viral Infection Activity. Issue 2 (13th April 2020) - Chang, Tengyu; Guo, Mengmeng; Zhang, Wei; Niu, Jinzhi; Wang, Jin-Jun
Abstract: We report a new positive-sense single-stranded RNA (ss RNA+) virus from the brown citrus aphid Aphis citricidus . The 20, 300 nucleotide (nt)-long viral genome contains five open-reading frames and encodes six conserved domains (TM2, 3CLpro, TM3, RdRp, Zm, and HEL1). Phylogenetic analysis and amino acid sequence analysis revealed this virus might belong to an unassigned genus in the family Mesoniviridae. The presence of the virus was also confirmed in the field population. Importantly, analysis of the virus-derived small RNAs showed a 22-nt peak, implying that viral infection triggers the small interfering RNA pathway as antiviral immunity in aphids. This is the first report of a mesonivirus in invertebrates other than mosquitoes.